A literature review on cardiovascular risk in human immunodeficiency virus-infected patients: implications for clinical management - Gomes Neto,Mansueto (2013)
INTRODUCTION: In recent years, there has been growing concern about an increasing rate of cardiovascular diseases in human immunodeficiency virus-infected patients, which could be associated with side effects of highly active antiretroviral therapy. It is likely that the metabolic disorders related to anti-human immunodeficiency virus treatment will eventually translate into a increased cardiovascular risk in patients submitted to such regimens. OBJECTIVE: To evaluate if human immunodeficiency virus-infected patients receiving highly active antiretroviral therapy are at higher risk of cardiovascular diseases than human immunodeficiency virus infected patients not receiving highly active antiretroviral therapy, or the general population. RESEARCH DESIGN AND METHODS: We conducted a computer-based search in representative databases, and also performed manual tracking of citations in selected articles. RESULT: The available evidence suggests an excess risk of cardiovascular events in human immunodeficiency virus-infected persons compared to non-human immunodeficiency virus infected individuals. The use of highly active antiretroviral therapy is associated with increased levels of total cholesterol, triglycerides, low-density lipoprotein and morphological signs of cardiovascular diseases. Some evidence suggested that human immunodeficiency virus-infected individuals on highly active antiretroviral therapy regimens are at increased risk of dyslipidemia, ischemic heart disease, and myocardial infarction, particularly if the highly active antiretroviral therapy regimen contains a protease inhibitor. CONCLUSION: Physicians must weigh the cardiovascular risk against potential benefits when prescribing highly active antiretroviral therapy. Careful cardiac screening is warranted for patients who are being evaluated for, or who are receiving highly active antiretroviral therapy regimens, particularly for those with known underlying cardiovascular risk factors. A better understanding of the molecular mechanisms responsible for increased risk of cardiovascular diseases in human immunodeficiency virus-infected patients will lead to the discovery of new drugs that will reduce cardiovascular risk in human immunodeficiency virus-infected patients receiving highly active antiretroviral therapy.